Isothermal amplification using sequence-specific fluorescence detection of SARS coronavirus 2 and variants in nasal swabs - Les Jones; Hemant K Naikare; Yung-Yi C Mosley; Ralph A Tripp (BioTechniques, 2022)
Coronavirus disease 2019 is a public health challenge requiring rapid testing for the detection of infections and transmission. Nucleic acid amplification tests targeting SARS coronavirus 2 (CoV2) are used to detect CoV2 in clinical samples. Real-time reverse transcription quantitative PCR is the standard nucleic acid amplification test for CoV2, although reverse transcription loop-mediated isothermal amplification is used in diagnostics. The authors demonstrate a sequence-specific reverse transcription loop-mediated isothermal amplification-based nucleic acid amplification assay that is finished within 30 min using minimally processed clinical nasal swab samples and describe a fluorescence-quenched reverse transcription loop-mediated isothermal amplification assay using labeled primers and a quencher oligonucleotide. This assay can achieve rapid (30 min) and sensitive (1000 plaque-forming units/ml) fluorescence detection of CoV2 (WA1/2020), B.1.1.7 (Alpha) and variants of concern Delta (B.1.617.2) and Omicron (B.1.1.529) in nasal samples.